Hesperidin, a citrus flavonoid ameliorates hyperglycemia by regulating key enzymes of carbohydrate metabolism in streptozotocin-induced diabetic rats. (22nd November 2019) - Sundaram, R.; Nandhakumar, E.; Haseena Banu, H.
Abstract: The present study investigated the protective effect of hesperidin on carbohydrate metabolizing enzymes in streptozotocin-induced diabetic rats. Hesperidin was administered to streptozotocin-induced (40 mg/kg b.w.) diabetic rats at different dosages of (25, 50, 100 mg/kg b.w.) respectively for 30 days to evaluate its effect on fasting plasma glucose, insulin, glycosylated hemoglobin, hemoglobin, and carbohydrate metabolic enzymes. The plasma glucose levels were significantly reduced in a dose-dependent manner in hesperdin-treated group of rats when compared to the diabetic control rats. In addition, concomitant increase in hemoglobin and insulin levels and a decrease in glycosylated hemoglobin were observed in treated group of rats. The activities of the hepatic key enzymes of carbohydrate metabolism such as hexokinase and glucose-6-phosphate dehydrogenase were significantly increased, whereas glucose-6-phosphatase and fructose-1, 6-bisphosphatase were significantly decreased. Furthermore, hesperidin administration prevented the loss in body weight and improved the glycogen content in the hepatic tissue of diabetic animals by reinstating the activities of glycogen synthase and glycogen phosphorylase. These results showed that hesperidin has potential antihyperglycemic activity in streptozotocin-induced diabetic rats. This was further supported by the histological studies of pancreas and liver.